2023
DOI: 10.1042/etls20220111
|View full text |Cite
|
Sign up to set email alerts
|

Dinner date: Neisseria gonorrhoeae central carbon metabolism and pathogenesis

Abstract: Neisseria gonorrhoeae, the causative agent of the sexually transmitted infection gonorrhea, is a human-adapted pathogen that does not productively infect other organisms. The ongoing relationship between N. gonorrhoeae and the human host is facilitated by the exchange of nutrient resources that allow for N. gonorrhoeae growth in the human genital tract. What N. gonorrhoeae ‘eats' and the pathways used to consume these nutrients have been a topic of investigation over the last 50 years. More recent investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…The inflammatory environment triggered by chlamydial/gonococcal infections could perturb the homeostasis of the rectal bacterial communities, leading to the proliferation/ depletion of specific genera [31,32]. In addition, the nutritional requirements of CT and NG could alter specific metabolic pathways, enabling the preferential replication of some bacterial genera compared to others [34,35].…”
Section: Plos Onementioning
confidence: 99%
“…The inflammatory environment triggered by chlamydial/gonococcal infections could perturb the homeostasis of the rectal bacterial communities, leading to the proliferation/ depletion of specific genera [31,32]. In addition, the nutritional requirements of CT and NG could alter specific metabolic pathways, enabling the preferential replication of some bacterial genera compared to others [34,35].…”
Section: Plos Onementioning
confidence: 99%
“…To detect ambient acetate, intestinal enterocytes and other cell types contain G-protein-coupled receptors, which mediate most of the molecular effects of acetate (Hosmer et al 2023). One example is the fact that oral acetate may upregulate IFN-stimulated genes in the lung, leading to interferon-β (IFN-β) responses (Antunes et al 2019).…”
Section: Acetatementioning
confidence: 99%
“…Despite having the ability to encode a complete tricarboxylic acid (TCA) cycle, previous studies revealed Ngo's puzzling phenotype of restricting crucial TCA cycle enzymes, such as GltA and AcnB (Potter and Criss 2023a).Additionally, it does not have the ability to encode phosphofructokinase (PFK). To probe deeper into metabolic anomaly in the TCA cycle, the application of systems biology, particularly, genome-scale metabolic models (GEMs), provides a promising avenue, since it has been proven to answer unusual bacterial phenomena (Chowdhury et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Despite having the ability to encode a complete tricarboxylic acid (TCA) cycle, previous studies revealed Ngo’s puzzling phenotype of restricting crucial TCA cycle enzymes, such as GltA and AcnB (Potter and Criss 2023a). Additionally, it does not have the ability to encode phosphofructokinase (PFK).…”
Section: Introductionmentioning
confidence: 99%